Editorial - Avila Souza, Jeferson (Revista de Engenharia Térmica, 2024)
In terms of energy production and consumption, the modern world's needs have become more and more challenging. Electrical energy is required to power most of all current “gadgets”, as well as, large industrial equipment, and more recently, our cars, which are expected to become all-electric in the not so far future. Once electrical energy (actually any kind of energy) can not be created or destroyed, it must be converted from other forms of energy. Our economy is still dependent on fossil energy sources like coal, petroleum and gas, which may be directly used to heat our homes and keep our cars running, but also to be converted into electrical energy. The drop-back of these resources is that they are highly pollutant and a worldwide movement is trying to reduce its use. Many bio alternatives have been proposed to replace these energy sources with a certain level of success. They are renewable and may help to reduce the greenhouse gas emission problem, however, alone, they will not solve the problem. In Brazil, most of the electrical energy comes from hydroelectric plants which are clean, renewable and reliable sources, however produces some undesired environmental impacts, most of them during the power plant construction. There is also a limited amount of this kind of energy that can be exploited. In parallel, we have the clean and renewable wind and solar sources. Both extraction technologies have already reached a higher maturity level and their use has been increasing in recent years. There is a great potential for large generation plants and also for small units to be installed in domestic homes or small consumption centers. For sure, there are other energy sources that could be included in the discussion. Any emerging country, like Brazil, needs to increase its infrastructure and reach a higher level of technological development. Among many factors, energy is one of the most important ones. A key issue with the energy production is its cost, and to reduce production costs, technological advances are needed. A promising emerging country can not rely only on foreign knowledge (technology) to build its infrastructure. Moreover, sustainable development can only be achieved when technological advances are promoted by its universities and research groups in a close collaboration with the industrial sector. For every energy type above discussed, even those with a higher level of development, there is still room for new discoveries, new applications and improvements, which must be relentlessly pursued by the Brazilian scientific community. We must have a commitment to the country's future.